PENERAPAN MODEL MORAL REASONING BERBANTUAN MEDIA KARTU DILEMA UNTUK MENINGKATKAN SIKAP PEDULI LINGKUNGAN SISWA KELAS V PADA MATA PELAJARAN PENDIDIKAN PANCASILA - Nur Adma, Rindani; Syahrul Rizal, Muhammad; Aprinawati, Iis; Masrul; Ediputra, Kasman (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study was motivated by the low level of environmental care attitudes among fifth-grade students at SDM 027 Batubelah, as indicated by initial observation data across four indicators: cleaning trash bins (29.6%), cleaning the school environment (22.2%), maintaining the school garden (7.4%), and maintaining environmental cleanliness (44.4%). The objective of this study is to improve students' environmental care attitudes through the application of the Moral Reasoning model assisted by Dilemma Cards. This study is a Classroom Action Research (CAR) using the Kemmis & Taggart design, conducted in two cycles, each consisting of two sessions. The research subjects were 26 fifth-grade students at SDM 027 Batubelah. Data collection instruments included the